I Trattamenti Sanitari Obbligatori, ovvero del circoscritto limite della libertà di salute (TEST BioLaw Journal - Rivista di BioDiritto, 2021)
After a rapid examination of the contents of art. 32 Cost. (rights, freedoms and duties), the article examines in depth the assumptions and guarantees that the same constitutional provision, together with art. 2 of the Constitution, provides the basis for the so-called Compulsory Health Treatment. The analysis is supported by numerous legislative references and, above all, by the extensive constitutional jurisprudence intervened on the subject. Particular attention is devoted to vaccinations (mandatory or constituting the object of “burdens”), to health treatments “compulsory” as well as recent Italian legislative innovations represented by the so-called green pass (typical examples of aggravated charges).
Keywords: Right to health; compulsory health treatments; vaccinations; mental diseases; green pass